First annual meeting of stakeholders in pig genetics in Uganda - Marshall, Karen; Ouma, Emily A.; Kugonza, Donald; Businge, Martha; Kasoro, Isaac; Namatovu, Jane; Ahumuza, Ronnie (International Livestock Research Institute, 2024)
On 7 May 2024, a stakeholders’ workshop was held with actors in the pig genetics sector as part of the Sustainable Animal Productivity for improved Livelihoods, Nutrition and Gender Inclusion (SAPLING) project in Uganda. A total of 56 participants, 21 female and 35 males, including representatives from public and private sectors attended the workshop. The workshop's objectives were to (a) identify constraints and solutions to these, as well as new opportunities across the pig genetics value chain, (b) promote networking and linkages between different actors within the pig genetics value chain, and (c) consider, and give feedback on the proposed regulations for the Uganda Animal breeding Act 2001 titled ‘registration & certification of terrestrial breeders, premises, assisted reproductive technology service providers and breeding stock regulations 2024’ in relation to the pig sector . The key activities in the workshop included 1) mapping the constraints and opportunities within the pig genetics value-chain, 2) reviewing the new regulations on animal breeding and obtaining feedback on these, 3) a marketplace for sharing of goods and services offered by the participants, and 4) update talks by various key actors. Participants’ feedback from the constraints and opportunity exercise will be used to inform future SAPLING interventions while feedback on animal breeding regulations will be shared with the committee developing the guidelines. As an ongoing plan of action, participants proposed to hold such meetings yearly.